MOTIVASI EKSTRINSIK PADA DYSFUNCTIONAL BEHAVIOR, MORAL EQUITY SEBAGAI VARIABEL PEMODERASI - Fitriyani, Fara; Utami, Ika (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2018)
This study aims to examine how the individual tendency as subordinate in creating budgetary slack, which yields a higher budget recommendation than the initial budget estimate when subordinates are faced with the pressure of adherence from superior superior. In addition, this study also examines how subordinate tendencies that have high moral equity or low moral equity in generating budgets when subordinates are confronted with the pressure of obedience from superiors. The population of this study is subordinate in universities in Banten Province. Sampling method using purposive sampling with the number of samples that meet the criteria as many as 91 respondents. Questionnaires were tested with reliability test and validity test, then tested classical assumptions include normality test, multicollinearity test, and heteroscedasticity test. Then the hypothesis test is done by simple regression analysis and multiple regression analysis. The results showed that all the variables are reliable and valid and meet the classical assumption test. The result of the hypothesis analysis shows that the pressure of obedience affects budgetary slack and there is no interaction between obedience pressure and moral equity to budgetary slack.